Pulmonary emphysema not combined with lung fibrosis in systemic sclerosis. (November 2019) - Franconeri, Andrea; Marasco, Emiliano; Dore, Roberto; Codullo, Veronica; Calliada, Fabrizio; Disabella, Eliana; Meloni, Federica; Zanframundo, Giovanni; Montecucco, Carlomaurizio; Valentini, Adele; Cavagna, Lorenzo
Abstract: Interstitial Lung Disease (ILD) is a common finding of Systemic Sclerosis (SSc) mainly presenting in the form of Nonspecific Interstitial Pneumonia (NSIP) and deeply affecting patients' prognosis. Beside NSIP, other types of ILD have been reported. The most recently described pattern is the so-called Combined-pulmonary emphysema and lung fibrosis, characterized by the coexistence of both upper lobes centrilobular and paraseptal emphysema and lower lobes ILD. We presented three cases of patients with SSc, in which High Resolution Computed Tomography examinations showed emphysema with atypical distribution and radiological presentation, without or with mild signs of fibrosing lung disease, that stabilized after immunosuppressive treatment. Highlights: We described an SSc-pulmonary involvement in which findings were not typical neither for ILD nor for CPFE syndrome. Emphysematous changes prevail and begin in the lower lobes without macroscopic signs of fibrotic alterations. An early recognition of this pattern is crucial in order to modify modalities of follow-up and therapeutic decision..